2017
DOI: 10.1017/s1041610217001326
|View full text |Cite
|
Sign up to set email alerts
|

The detection, diagnosis, and impact of cognitive impairment among inpatients aged 65 years and over in an Irish general hospital – a prospective observational study

Abstract: Cognitive impairment is pervasive and under-recognized in the acute hospital and impacts negatively on patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Furthermore, 1 study reported a 72% lower odds for PWD to have a LOS of 10 days or more compared to PwoD (95% CI: 0.1‐0.4) . With exception of 1 study conducted in Ireland, the remaining studies across Europe reported a longer LOS for PWD of up to 22 days . Within countries, the different studies were consistent in reporting a longer LOS for PWD compared to PwoD; however, the difference in the LOS varied up to 13 days …”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Furthermore, 1 study reported a 72% lower odds for PWD to have a LOS of 10 days or more compared to PwoD (95% CI: 0.1‐0.4) . With exception of 1 study conducted in Ireland, the remaining studies across Europe reported a longer LOS for PWD of up to 22 days . Within countries, the different studies were consistent in reporting a longer LOS for PWD compared to PwoD; however, the difference in the LOS varied up to 13 days …”
Section: Resultsmentioning
confidence: 93%
“…The mean overall score was 5.8. Eleven studies had a small sample size (range: 42‐395), were conducted in a single hospital (‐ward), or showed a sex distribution not representative of the PWD population . Thirty‐three studies met the criteria for comparability based on design or analysis, thereof 8 studies controlled or matched for 1 factor and 25 studies for at least 2 factors .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In most studies, CI or dementia increased length of hospital stay (LOS) . (Table ) Patients with DSD had longer mean LOS than those with dementia or delirium alone .…”
Section: Resultsmentioning
confidence: 99%
“…Patients with CI are frequently discharged to nursing/residential homes . Dementia predicts of institutionalisation (odds ratio 2.14 [1.24‐3.70]), although less so in ambulatory care sensitive conditions .…”
Section: Resultsmentioning
confidence: 99%